2003
DOI: 10.1007/s00220-002-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Binding in Non-Relativistic QED

Abstract: We consider a Pauli-Fierz Hamiltonian for a particle coupled to a photon field. We discuss the effects of the increase of the binding energy and enhanced binding through coupling to a photon field, and prove that both effects are the results of the existence of the ground state of the self-energy operator with total momentum P = 0.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…As in all previous papers [9,6,3,2,4], our method is asymptotic in α. Therefore, the problem of establishing the enhanced binding effect and estimating its strength for the physical value of α ≈ 1/137 still remains open.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As in all previous papers [9,6,3,2,4], our method is asymptotic in α. Therefore, the problem of establishing the enhanced binding effect and estimating its strength for the physical value of α ≈ 1/137 still remains open.…”
Section: Introductionmentioning
confidence: 95%
“…Dressing a charged particle with photons increases the ability of a potential to confine it. For the Pauli-Fierz operator which describes a nonrelativistic particle interacting with a radiation field, this effect was proved for small values of the fine structure constant α, first under the simplifying assumption that the spin of the particle is absent [9], and later generalized to the case of a particle with spin [6,3]. In [2], it was shown that the effect of the enhanced binding is asymptotically small in α in the sense that the binding threshold for the Pauli-Fierz operator tends to the binding threshold for the corresponding Schrödinger operator as α tends to zero.…”
Section: Introductionmentioning
confidence: 99%
“…The leading term of the ground state energy was demonstrated to be of order O(α 2 ) (up to normal ordering) in [8], and explicitly determined, with a rigorous error bound of order O(α 3 ). A similar result was subsequently obtained for the spin 1 2 case in [4].…”
Section: Introductionmentioning
confidence: 97%
“…They showed that there exists a constant α * such that the enhanced binding occurs for arbitrary values of coupling constants |α| > α * . Hainzl, Vougalter and Vugalter [7] proved that there exists a sufficiently small constant ρ > 0 such that the enhanced binding occurs for all α ∈ (0, ρ] in the Pauli-Fierz model without the dipole approximation. Benguria and Vugalter [4] showed that the enhanced binding does not occur for sufficiently small coupling constants in the Pauli-Fierz model.…”
Section: Introductionmentioning
confidence: 99%